FAKTOR-FAKTOR YANG MENENTUKAN HASIL PRODUKSI PADI SAWAH DI DESA MAKARTI KECAMATAN KAO BARAT KABUPATEN HALMAHERA UTARA - Dedison ., Saketa; Oktavianus ., Porajouw; Elsje Pauline Manginsela (Sam Ratulangi University, 2018)
This study aims to describe the determinants of land area, capital and labor to the production of lowland rice. This research was conducted in Makarti Village, West Kao District, North Halmahera Regency. This research lasted for three months, namely from March to May 2017. Sampling in this study used proportional area random sampling. The data used in this study were primary data and secondary data. The results of the study indicated that the area of land determines the yield of production because by adding land area the yield will tend to increase. Capital determines production results because by adding capital it can increase production. Labor also determines the yield of rice. These three factors are closely related and mutually supportive in increasing the yield of rice cultivation. This study concludes that the determinants of land area, capital, and labor tend to increase the yield of rice production.*epm*